Better late than never [large type] - McKinlay, Jenn (McKinlay, Jenn. Library lover's mysteries., 2017)
"A decades-overdue book puts library director Lindsey Norris hot on the trail of a cold case when she discovers the book was checked out by a schoolteacher on the day she was murdered twenty years ago"--